2005
DOI: 10.1136/bmj.330.7487.334
|View full text |Cite
|
Sign up to set email alerts
|

Rectal artemether versus intravenous quinine for the treatment of cerebral malaria in children in Uganda: randomised clinical trial

Abstract: Objective To compare the efficacy and safety of rectal artemether with intravenous quinine in the treatment of cerebral malaria in children. Design Randomised, single blind, clinical trial. Setting Acute care unit at Mulago Hospital, Uganda's national referral and teaching hospital in Kampala. Participants 103 children aged 6 months to 5 years with cerebral malaria. Intervention Patients were randomised to either intravenous quinine or rectal artemether for seven days. Main outcome measures Time to clearance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 15 publications
2
31
1
Order By: Relevance
“…The longer parasite clearance times in the study in Niger [15] may also have occurred because of the longer intervals in assessing serial parasite densities. Our study also revealed an evidently shorter trend in time to parasite clearance than did an earlier study in Uganda by Aceng et al [14] that used rectal artemether (43.1 h vs. 54.2 h;…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The longer parasite clearance times in the study in Niger [15] may also have occurred because of the longer intervals in assessing serial parasite densities. Our study also revealed an evidently shorter trend in time to parasite clearance than did an earlier study in Uganda by Aceng et al [14] that used rectal artemether (43.1 h vs. 54.2 h;…”
Section: Discussioncontrasting
confidence: 54%
“…The explanation for this may be the systematic use of paracetamol and tepid sponging for temperature control in our study. Our study also had shorter fever clearance times, compared with some studies using rectal artemether [14,20]. The explanation for this may be the more erratic absorption of artemether suppositories [21].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Rectal artesunate is unlikely to challenge either parenteral artesunate or quinine in hospital practice, but it may have a significant role in pre-hospital settings, especially in rural parts of Africa where the bulk of malaria deaths occur. A trial in Uganda comparing rectal artemether with intravenous quinine showed a trend towards lower mortality, faster parasite clearance and faster time to defervescence in the artemether arm compared with the quinine arm; however, these results failed to reach statistical significance [36] and rectal artesunate may well fare better [37]. A recent multicenter trial of rectal artesunate used in a rural setting has recently been completed and will report shortly.…”
Section: Drug Safetymentioning
confidence: 92%
“…In this issue Aceng et al report a randomised trial of intravenous quinine compared with rectal artemether in cerebral malaria 3. They found that the effects of intravenous quinine and rectal artemether were comparable, both in terms of efficacy and time to recover.…”
mentioning
confidence: 99%